Targeting Listeria monocytogenes consensus sequence of internalin genes using an antisense molecule. (November 2019) - Kalani, Behrooz Sadeghi; Najafi, Mohammad; Mohammadzadeh, Rokhsareh; Razavi, Shabnam; Ohadi, Elnaz; Norkhoda sadeghifard,; Irajian, Gholamreza
Abstract: As an intracellular pathogen, Listeria monocytogenes can enter host cells where it can replicate and escape detection and eradication by the host immune response making the clearance of infection very challenging. Furthermore, with the advent of antimicrobial resistance, the need for alternative targets is inevitable. Internalin proteins are crucial to this bacterium as they contribute to bacterial entry to the systemic circulation. In this study, we targeted a highly conserved region of these proteins by an antisense sequence that was covalently conjugated to the cell penetrating peptides (CPP) to overcome the challenging delivery barriers. Then, we evaluated the efficiency of this construct in vitro. We also assessed the antigenicity, cytotoxicity, and probability of apoptosis induction by this construct. The studied CPP-PNA inhibited bacterial growth and suppressed the mRNA expression of internalins in a dose-dependent manner. In addition, at all studied concentrations, CPP-PNA significantly reduced the invasion rate of L. monocytogenes in the examined cell lines. Moreover, different concentrations of CPP-PNA did not have a significant antigenic, cytotoxic, and apoptotic properties compared to the control. These results suggest the effectiveness of CPP-antisense in targeting the mRNAs of internalins for various research, therapeutic and preventive purposes. However, additional research is required to evaluate the potency, safety, and pharmacokinetics of this compound for the prevention and treatment of listeriosis. Highlights: L. monocytogenes  is an invasive foodborne pathogen that causes listeriosis with a 20–30% case fatality rate. Internalin proteins are crucial to pathogenesis of this bacterium. We targeted a highly conserved region of these proteins by an antisense sequence. The studied CPP-PNA inhibited bacterial growth and suppressed the mRNA expression of internalins in a dose-dependent manner. The CPP-PNA significantly reduced the invasion rate of  L. monocytogenes  in the examined cell lines.Moreover, the CPP-PNA did not have a significant antigenic, cytotoxic, and apoptotic properties compared to the control.